Faeth fiadha. "Lorica" świętego Patryka - Bulas, Ryszarda (Vox Patrum, 2004)
The article treats of the most famous sort of Irish protective prayer, which name is lorica (breastplate). The author talks over this kind of prayer and inserts its translation. Next, on the base of article of O’Donoghue, the author analyzes every stanza of S. Patrick’s lorica. First and eight stanza tells about Trinity and God, in the second and second the power of Christ is invoked in all its main manifestations: his birth, his baptism, his death and burial, his resurrection and his coming in judgment. The third stanza descends from the sphere of deity to the world of the first creation - angels. The fourth stanza dips down from heavenly host to the visible cosmos in its spheres and elements: sun, moon, and firmament, and the four elements: fire, air, water and earth. In the fifth stanza we are back at the source of creation, a natural progression from the invocation of created nature in the fourth stanza. The sixth stanza tells about spells cast by women and blacksmiths and druids.